A new unified theory of psychology - Henriques, Gregg; SpringerLink (Online service). (New York Springer, 2011)
"Following the demise of the so-called grand theories offered by luminaries like Sigmund Freud, B. F. Skinner, and Carl Rogers, the field of psychology largely gave up its early aspirations to paint a broad picture of the human condition, and now the discipline focuses primarily on empirical problems that have a relatively narrow scope. The consequence has been a proliferation of interesting findings with no real capacity to answer big questions or to generate a shared general understanding of the human condition. This book seeks to change the status quo and offers up a new unified theory of psychology that redefines the science and the profession and paints a new picture of human nature in the process."--Publisher's description.
pt. 1. Introduction and overview -- pt. 2. The four pieces that make up the unified theory -- pt. 3. Solving the problem of psychology -- pt. 4. Conclusion.
Electronic reproduction.
Keywords: Psychology; Psychology -- Philosophy; Electronic books